PENGARUH LOKASI, VARIASI PRODUK DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG MINA DALUNG - Anak Agung Made Karma Wijaya; Ni Putu Cempaka Dharmadewi Atmaja; Daniel Manek (Jurnal Bakti Saraswati (JBS), 2024)
Facing intense business competition, understanding consumer behavior is crucial. This research aims to identify the influence of location, product variety, and electronic word of mouth on purchasing decisions at Warung Mina Dalung. Questionnaires were distributed to 100 respondents using accidental sampling technique. Data analysis used multiple linear regression. The research results show that location has a positive and significant effect on purchasing decisions, meaning that the better the location, the purchasing decisions at Warung Mina Dalung will also increase. Product variations have a positive and significant effect on purchasing decisions, meaning that the better the product variations, the purchasing decisions at Warung Mina Dalung will also increase. Electronic word of mouth has a positive and significant effect on purchasing decisions for Warung Mina Dalung consumers, meaning that as electronic word of mouth increases, purchasing decisions for Warung Mina Dalung employees will increase. Companies are advised to evaluate locations, survey satisfaction, product variety, quality, supplier collaboration, and increase e-WOM through interesting content on social media. In the next research, consider the variables of price, promotion and consumer satisfaction, and compare them with similar stalls.